Knowledge Management in the Sharing Economy Cross-Sectoral Insights into the Future of Competitive Advantage (Knowledge Management and Organizational Learning,, 2018)
This volume explores the challenge of engaging knowledge management in a sharing economy. In a hyper-competitive business environment, everything tends to be digital, virtual and highly networked, which raises the issue of how knowledge management can support the decision whether or not to share strategic resources or capabilities. The book answers questions such as: to what extent does the sharing economy preserve or compromise the competitive advantage of organizations? And what are the knowledge-management strategies for competitive, yet cautious sharing dynamics?